An Alternative Technique for Surgical Management of Poststernotomy Osteomyelitis and Reconstruction of the Sternal Defect. (3rd March 2013) - Konofaos, Petros; Spartalis, Eleftherios; Karagkiouzis, Grigorios; Kampolis, Christos; Tomos, Periklis
Abstract : Introduction. Sternal osteomyelitis with or without mediastinal infection is a severe and rare complication of median sternotomy. In this paper, an alternative technique for the reconstruction of sternal defects with the use of bilateral pectoralis major pedicled muscle flaps is presented. Case presentation. A 70-year-old man with the diagnosis of poststernotomy osteomyelitis underwent reconstruction of his sternal defect with the use of bilateral pectoralis major muscle flaps. The patient had an uneventful recovery, and the physical examination revealed a normal range of motion for both upper limbs and sternal stability. Conclusion. The proposed technique incorporates a simple mobilization of the two pectoralis major muscles to be used as flaps to fill the sternal defect without the need for humeral detachment or a second cutaneous incision. Using this technique, a muscular implant is made that seals the dead space, which has no tension due to the presence of a second layer. Postoperative results are excellent, not only regarding infection and functionality but also from an aesthetic point of view.